Changes in provision of extended community pharmacy services in Aotearoa New Zealand, 2018 to 2022 - Tara Officer; Janet McDonald; Mona Jeffreys; Jacqueline Cumming; Lynne Russell; Eileen McKinlay; Jonathan Kennedy; Ausaga Fa’asalele Tanuvasa; Caroline Morris (BMC Health Services Research)
Abstract Background Recognition is growing of the contributions community pharmacists make to the primary health care team, as their role shifts from a traditional dispensing focus to greater emphasis on fully applying their clinical skills. Some extended pharmacist services (e.g., vaccinations) are becoming increasingly common in New Zealand (Aotearoa). Community pharmacies provided key services during the COVID-19 response. Methods An online survey was sent to community and intern pharmacists in 2022, regarding delivery of extended services and enablers and barriers to service provision, to look at changes since a 2018 survey. New questions were included regarding pharmacy services during the COVID-19 pandemic. Descriptive analyses were conducted, and comparisons made between reported proportions in the 2018 and 2022 surveys. For questions related to attributes of pharmacies rather than pharmacists, we weighted the data by the inverse of the number of pharmacists in the pharmacy. Results A total of 64 pharmacists and 25 interns responded to the survey. The most common services for which pharmacists were accredited were the provision of the emergency contraceptive pill (95%), sildenafil (94%), trimethoprim (88%) and immunisations (80%). There was an increase from 2018 to 2022 in the proportion of pharmacists who were accredited to provide selected oral contraceptives and immunisations. As in 2018, interns showed strong interest in gaining accreditation for all extended services. Enablers and barriers to offering extended services did not change materially between 2018 and 2022, other than a greater proportion of pharmacists reporting that they were too busy dispensing to offer more services (an increase from 46 to 63%, P = 0.033). Almost all (98%) reported that “COVID increased the levels of stress at work”, 94% that “workload has increased”, and 90% that “home delivery services increased.” Sixty-nine percent of pharmacists and 73% of interns reported work stress negatively affecting their wellbeing. Conclusions Most pharmacists want to work at the top of their scope of practice and are accredited to offer a range of extended services. However, their ability to focus on more patient-facing roles continues to be constrained by the time they spend dispensing. Adequate remuneration for services provided remains a concern.